Identifikasi Pariwisata di Kecamatan Medan Barat Kota Medan dan Usulan Pengembangannya dalam Lingkup Arsitektur - Nur Al Hasanah; Mia Prihatini; Gabriel Manalu; Robby Pratama; Azizur Rohman N (Arsil Media, 2023)
The tourism industry is one of the industries that has an important role in the national development of various countries today where in 2017, globally the tourism industry has driven the progress of the lives of millions of people by encouraging economic growth, creating jobs, reducing poverty, and accelerating development and strengthening tolerance. In this condition, Indonesia is also one of the countries that has an impact on these developments. Where the tourism sector in 2016 showed development and continued to increase and make an increasingly significant contribution to the national Gross Domestic Product (GDP). Seeing this potential, tourism development is starting to become one of the leading programs in regional development, in which case this discussion will focus on the development of tourism in one of the districts in the city of Medan. Tourism development that is planned and managed in a sustainable manner based on the community will be able to contribute to local revenue (PAD) and create jobs.